Avaliação da qualidade do sono, fadiga e saúde mental no período de pandemia da COVID-19 em mulheres brasileiras, com e sem doenças reumatológicas - Santos, Gabriel Bernardi dos (Universidade Federal de São Carlos, 2022)
Introduction: The COVID-19 pandemic has caused several changes at the global level due to its consequent restrictions and the high level of stress caused by the fear of infection itself regarding the decrease in social interaction, with implications mainly for the most vulnerable population. Objectives: The objectives were: to evaluate women with and without rheumatological diseases during the pandemic period in Brazil, in relation to sleep quality, fatigue and mental health (anxiety, depression and anxiety and depression), to compare these two groups, to verify if between there are worse outcomes for women with rheumatologic diseases for a given group of diseases, and to seek associations between women without rheumatologic diseases, in relation to the evaluated outcomes, and to establish what would be the factors that lead to a worsening of these. Methods: Brazilian women participated in this study with and without rheumatologic diseases, aged 18 to 65 years, evaluated through the questionnaires: Pittsburgh Sleep Quality Index, the Fatigue Severity Scale and Hospital Depression and Anxiety Scale. The group of women without diseases underwent a second evaluation. Data were presented descriptively, and the groups were compared using the chi-square test for categorical variables and the Mann Whitney test for quantitative variables. In the group of healthy women, the comparison between the two evaluation moments was performed using the McNemar test. A logistic regression was performed to search for possible associations between the variables (α ≤ 0.05). Results: The group of women with rheumatologic diseases showed a worsening in the quality of sleep, fatigue and mental health when compared to women without diseases (p<0.01). Among the group of women with rheumatologic diseases, fibromyalgia had one for all outcomes (p<0.01). For healthy women, there was a significant increase between the two collection times for the fatigue variable (p ≤ 0.05). In the first assessment, depression (OR: 2.39; 95% CI: 1.14-4.99), anxiety (OR: 2.68; 95% CI: 1.37-5.22) and sleep quality (OR: 4.01; 95% CI: 1.71-9.67) were associated with fatigue, and in the second, depression (OR: 2.93; 95% CI: 1.19-7.18) and anxiety (OR: 2.93; 95% CI: 1.19-7.18): 2.69; 95% CI: 1.27-5.71). Conclusion: During the COVID-19 pandemic in Brazil, women with rheumatological diseases experienced a worse quality of sleep, fatigue and aspects of mental health when compared to women without rheumatological diseases and among those with some disease, women with fibromyalgia are the most affected in all respects in the period evaluated. In addition, it is concluded that a high rate of women is experiencing an impact on biopsychosocial aspects during the COVID-19 pandemic, with some of these worsening, such as fatigue symptoms, which were associated with depression, anxiety, and worse quality of life. of sleep in the first year of the pandemic, remaining associated with depression and anxiety in the second year of the pandemic in the country.
Assessment of sleep quality, fatigue and mental health during the COVID-19 pandemic in Brazilian women, with and without rheumatologic diseases
Keywords: Saúde da mulher; Reumatologia; Qualidade de vida; Saúde coletiva; Women's Health; Rheumatology; Quality of life; Public health; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL